Cognitive Behavior Therapy dalam Menurunkan Kecemasan pada Pasien Kanker Payudara - Lia Fadlilah; Tintin Sukartini; Hanik Endang Nihayati; Jaka Surya Hakim; Elin Hidayat (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of cognitive behavior therapy in reducing anxiety in patients with breast cancer. The research method used in this research is a systematic review through the PICOT method by searching using the CINAHL, SAGE, SCOPUS, and Proquest databases. The study results showed that most revealed a positive impact of cognitive behavior therapy on reducing anxiety in patients with breast cancer. In conclusion, the benefits provided by this therapy can help overcome the stress experienced by patients with breast cancer. Keywords: Cognitive Behavior Therapy, Breast Cancer, Anxiety